A Lakeshore Modification Index and its association with benthic invertebrates in alpine lakes. Issue 2 (22nd April 2012) - Peterlin, Monika; Urbanič, Gorazd
ABSTRACT Lakeshores are under increasing pressure from human activities, which cause extensive hydromorphological alterations. In this article, a method is described for assessing those alterations by using physical criteria developed in relation to the response by the lakeshore ecosystem, using benthic invertebrates as indicators. Two alpine lakes (Lake Bled and Lake Bohinj, Slovenia) were used as a case study. Both lakes are subjected to varying levels of physical alterations and lakeshore uses, which are described using alteration variables for four lakeshore zones: littoral zone, shoreline zone, riparian zone and lakeshore region. On the basis of these four variables, a Lakeshore Modification Index (LMI) was developed as a weighted sum of all variables. The weights were based on each variable's explanatory power regarding the distribution of benthic invertebrate taxa using canonical correspondence analyses. Both the LMI and all four lakeshore zone alteration variables showed significant (p < 0.01) negative correlations with species richness, but the LMI showed the strongest correlation (Pearson r = −0.086, p < 0.01). Differences existed in the level of alteration of the two lakes, with Lake Bled being more altered than Lake Bohinj; Lake Bled also exhibited the highest values for all four alteration variables and the highest LMI score. With the use of a classification system with five equidistant LMI classes, a difference was observed between the lakes in the distribution of LMI classes (two‐sample Kolmogorov–Smirnov test Z = 5.714, p < 0.01). An assessment and classification of lakeshore modifications based on physical criteria, similar to that given by the LMI, can provide an important tool for lake management in practice, where a reliable method for assessing pressures is needed to support decision‐making. Copyright © 2012 John Wiley & Sons, Ltd.